2019
DOI: 10.3389/fbioe.2019.00229
|View full text |Cite
|
Sign up to set email alerts
|

The White-Rot Basidiomycete Dichomitus squalens Shows Highly Specific Transcriptional Response to Lignocellulose-Related Aromatic Compounds

Abstract: Lignocellulosic plant biomass is an important feedstock for bio-based economy. In particular, it is an abundant renewable source of aromatic compounds, which are present as part of lignin, as side-groups of xylan and pectin, and in other forms, such as tannins. As filamentous fungi are the main organisms that modify and degrade lignocellulose, they have developed a versatile metabolism to convert the aromatic compounds that are toxic at relatively low concentrations to less toxic ones. During this process, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 78 publications
(112 reference statements)
1
14
0
2
Order By: Relevance
“…This variability is strain-specific and occurs even when the strain is subjected to similar experimental conditions such as performed here ( Whiting and Golden, 2002 ; Freire et al, 2018 ). Also in agreement with our results, several reports indicate that, once the mycotoxins have reached a maximum production, a decline of its levels occurs, possibly because of the ability of the fungus to degrade or convert the mycotoxins into other metabolites ( Freire et al, 2018 ; Kowalczyk et al, 2019 ). Furthermore, Greeff-Laubscher et al (2020) showed that the level of mycotoxin production by a fungus can vary largely within the replicates of a trial as well as length of time of incubation of the fungus, with episodes of levels increasing and decreasing over the whole period.…”
Section: Resultssupporting
confidence: 93%
“…This variability is strain-specific and occurs even when the strain is subjected to similar experimental conditions such as performed here ( Whiting and Golden, 2002 ; Freire et al, 2018 ). Also in agreement with our results, several reports indicate that, once the mycotoxins have reached a maximum production, a decline of its levels occurs, possibly because of the ability of the fungus to degrade or convert the mycotoxins into other metabolites ( Freire et al, 2018 ; Kowalczyk et al, 2019 ). Furthermore, Greeff-Laubscher et al (2020) showed that the level of mycotoxin production by a fungus can vary largely within the replicates of a trial as well as length of time of incubation of the fungus, with episodes of levels increasing and decreasing over the whole period.…”
Section: Resultssupporting
confidence: 93%
“…Crepidotus praecipuus is recorded as an endemic species of New Zealand, and this is the first time it has been recorded outside of New Zealand (https:// inaturalist.nz). Dichomitus squalens is a white-rot basidiomycete that produces diverse extracellular enzymes for lignocellulose degradation and oxidative enzymes to act on lignin [23][24][25]. The extracts from cultivated Trametes lactinea significantly inhibit the activities of lipoxygenase and hyaluronidase [26].…”
Section: Resultsmentioning
confidence: 99%
“…Due to their broad substrate specificity, laccases also are attractive biocatalysts for a wide range of biotechnology applications. The previous studies have shown that lcc3 is highly expressed by D. squalens in various cultivation conditions [32,34,54], which made it an interesting target to study its role in vivo in more detail. The protoplast mixture was supplied with 7 and 10 µg of ssODNs for the repair of cuts introduced in the sdi1 and lcc3 loci, respectively, while the total amount of Cas9 and gRNA used to assemble RNPs remained unchanged.…”
Section: Coediting Allows Selection Of Mutants With Edits At the Gene Of Interest In The Wild-type D Squalensmentioning
confidence: 99%
“…Manganese peroxidases (MnPs) are key enzymes for lignin degradation and uniquely produced by white-rot fungi [31]. As the D. squalens MnP2 encoding gene has been reported to be highly expressed in several wood and other plant biomass containing cultures [32,34,54,55], we were interested to target it to obtain a strain that possibly has an altered ability for lignocellulose conversion. In this case, one out of 10 carboxin-resistant transformants showed the expected EcoRI restriction pattern.…”
Section: Coediting Allows Selection Of Mutants With Edits At the Gene Of Interest In The Wild-type D Squalensmentioning
confidence: 99%
See 1 more Smart Citation